A New Notion of Fuzzy Local Function and Some Applications. (13th June 2022) - Taha, I. M.; Abbas, S. E.
Abstract : In this paper, a new notion of fuzzy local function called r -fuzzy local function is introduced, and some properties are given in a fuzzy ideal topological space X, τ, ℓ in Šostak sense. After that, the concepts of fuzzy upper (resp., lower) almost ℓ -continuous, weakly ℓ -continuous, and almost weakly ℓ -continuous multifunctions are introduced. Some properties and characterizations of these multifunctions along with their mutual relationships are discussed with the help of examples.